1992
DOI: 10.1111/j.1365-3148.1992.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody binding to blood group antigens in relation to temperature: scanning electron microscopy of immunogold‐labelled erythrocytes

Abstract: Binding patterns of mouse monoclonal antibodies (mAb) to P1, Pk, N, I, H, Y or A antigens were visualized in the backscatter electron imaging mode of a scanning electron microscope by indirect immunogold labelling. Experiments were performed at room temperature (RT) and at 4 degrees C. In experiments with anti-P1 and anti-Pk, clusters of immunolabelling particles dominated the immunolabelling pattern much more at RT than at 4 degrees C. By contrast, no clustering was seen with anti-N, even at RT. Clustering wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It is well established by agglutination [l, 231 and immunolabelling [3,4] that there are truly A-negative erythrocytes in individuals of phenotype A3. Immunolabelling studies have shown, furthermore, that cell-to-cell varia-234 HeierMamorWCalkovskA/Sandin/Kornstad A Antigens in Weak A Subgroups tion of antigen amount is a general feature of all carbohydrate blood group antigens [3][4][5]14,24]. Truly A-negative cells may exist even in A2 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established by agglutination [l, 231 and immunolabelling [3,4] that there are truly A-negative erythrocytes in individuals of phenotype A3. Immunolabelling studies have shown, furthermore, that cell-to-cell varia-234 HeierMamorWCalkovskA/Sandin/Kornstad A Antigens in Weak A Subgroups tion of antigen amount is a general feature of all carbohydrate blood group antigens [3][4][5]14,24]. Truly A-negative cells may exist even in A2 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In each experiment, 160-300 cells were counted. Similar semiquantitation of labeling has been carried out previously on single labeled cells Heier et al, 1988Heier et al, , 1992aSoligo et al, 1985).…”
Section: Labeling Protocolmentioning
confidence: 86%
“…All labelings using anti-H were incubated a t 4°C (277"K), since anti-H was found to give clusters of labeling particles when incubated at room temperature, 20°C (293°K). The anti-A was incubated at 20°C (293"K), since no difference in labeling pattern or strength was found between the two temperatures (Heier et al, 1992a). Preparation for SEM (BEI).…”
Section: Labeling Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…cells carry in addition the 'repetitive A' type 3 chains [2], This is due to molecular differences between the A2 and A1 alleles, which makes the N-acetylgalactosamine transferase in A2 cells less effective than that in Ai cells [18]. Small amounts of type 1 [19] and 4 [20] A chains have been detected on tion of antigen amount is a general feature of all carbo hydrate blood group antigens [3][4][5]14,24], Truly A-negative cells may exist even in A2 individuals. It is therefore not unexpected to find phenotypic variants in which the actual carbohydrate antigen is developed on a few cells only.…”
Section: Abo Genotypingmentioning
confidence: 99%